Digital connectivity – social impact : 51st Annual Convention of the Computer Society of India, CSI 2016, Coimbatore, India, December 8-9, 2016, Proceedings /: 51st Annual Convention of the Computer Society of India, CSI 2016, Coimbatore, India, December 8-9, 2016, Proceedings. (2016) - Unknown
No abstract available